MARKET SEGMENTATION ANALYSIS AND POSITIONING TO INCREASE PRODUCT COMPETITIVENESS IN THE GLOBAL MARKET - Nugroho, Dony Ari (Ridwan Institute, 2024)
This study aims to find out how to increase product competitiveness in the global market through the analysis of market segmentation and positioning. The study employs a qualitative approach, utilizing a systematic literature review (SLR) design. The data is analyzed through identification, classification, conclusion drawing, and verification. The research contribution lies in its focus on enhancing the competitiveness of products in a highly competitive global environment by analyzing market segments and positioning strategies. This study provides valuable insights and practical guidelines for businesses seeking to optimize their market presence and differentiate their products in an ever-evolving era of globalization. In addition, the study explores the impact of cultural and local adaptation on the success of positioning strategies in diverse markets.